Tumor-Associated Lymphatic Vessels Upregulate PDL1 to Inhibit T-Cell Activation - Dieterich, Lothar C.; Ikenberg, Kristian; Cetintas, Timur; Kapaklikaya, Kübra; Hutmacher, Cornelia; Detmar, Michael (Frontiers in Immunology, 2017)
Tumor-associated lymphatic vessels play multiple roles during tumor progression, including promotion of metastasis and regulation of anti-tumor immune responses by delivering antigen from the tumor bed to draining lymph nodes. Under steady-state conditions, lymph node resident lymphatic endothelial cells have been found to maintain peripheral tolerance by directly inhibiting autoreactive T-cells. Similarly, tumor-associated lymphatic endothelium has been suggested to reduce anti-tumor T-cell responses, but the mechanisms that mediate this effect have not been clarified. Using two distinct experimental tumor models, we found that tumor-associated lymphatic vessels gain expression of the T-cell inhibitory molecule PDL1, similar to lymph node resident lymphatic endothelial cells, whereas tumor-associated blood vessels downregulate PDL1. The observed lymphatic upregulation of PDL1 was likely due to IFN-g released by stromal cells in the tumor microenvironment. Furthermore, we found that blocking PDL1 results in increased T-cell stimulation by antigen-presenting lymphatic endothelial cells in vitro. Taken together, our data suggest that peripheral, tumor-associated lymphatic endothelium contributes to T-cell inhibition, by a mechanism similar to peripheral tolerance maintenance described for lymph node resident lymphatic endothelial cells. These findings may have clinical implications for cancer therapy, as lymphatic expression of PDL1 could represent a new biomarker to select patients for immunotherapy with PD1 or PDL1 inhibitors.